Acetylcholinesterase Inhibition Activity of Hippeastrum papilio (Ravenna) Van Scheepen (Amaryllidaceae) Using Zebrafish Brain Homogenates - Luciana R. Tallini; Camila Rockenbach da Silva; Tatiana Jung; Elen de Oliveira Alves; Samira Leila Baldin; Miriam Apel; Luis F. S. M. Timmers; Eduardo Pacheco Rico; Jaume Bastida; José Angelo S. Zuanazzi (Life, 2023)
The Amaryllidaceae family constitutes an interesting source of exclusive alkaloids with a broad spectrum of biological activity. Galanthamine, the most relevant one, has been commercialized for the palliative treatment of Alzheimer’s disease symptoms since 2001 due to its potential as an acetylcholinesterase (AChE) inhibitor. In vitro screenings against AChE by applying different Amaryllidaceae species and alkaloids have been reported in the literature; however, they are usually carried out using purified market enzymes. The main goal of this work is to evaluate the AChE inhibitory potential of Hippeastrum papilio (Amaryllidaceae) extracts using zebrafish brain homogenates. The biological assays show that the H. papilio bulb extracts present an interesting AChE inhibitory activity in comparison with the positive reference control galanthamine (IC50 values of 1.20 ± 0.10 and 0.79 ± 0.15 μg/mL, respectively). The chemical profile of H. papilio shows that this species has a high amount of galanthamine, which may contribute to the inhibitory effect on AChE activity of zebrafish brains. Computational experiments were used to build the model for zebrafish AChE and to evaluate the interactions between galanthamine and the enzymic active site. This work suggests that zebrafish could represent an important model in the search for bioactive molecules from the Amaryllidaceae family for the treatment of Alzheimer’s disease.